Navigating Hereditary Hearing Loss: Pathology of the Inner Ear - Nicolson, Teresa (Frontiers in Cellular Neuroscience, 2021)
Inherited forms of deafness account for a sizable portion of hearing loss among children and adult populations. Many patients with sensorineural deficits have pathological manifestations in the peripheral auditory system, the inner ear. Within the hearing organ, the cochlea, most of the genetic forms of hearing loss involve defects in sensory detection and to some extent, signaling to the brain via the auditory cranial nerve. This review focuses on peripheral forms of hereditary hearing loss and how these impairments can be studied in diverse animal models or patient-derived cells with the ultimate goal of using the knowledge gained to understand the underlying biology and treat hearing loss.